Genetic diversity of parthenocarpic genotypes shrubby squash using molecular genetic markers - Méndez-López, Alonso; Villanueva-Verduzco, Clemente; Rojas-Martínez, Reyna Isabel; Sahagún-Castellanos, Jaime; Colinas-León, M. Teresa; Sánchez-Vega, Miriam (Revista Mexicana de Ciencias Agrícolas, 2019)
The production of squash (Cucurbita pepo L.) for vegetables or zucchini under cover presents difficulties due to the lack of pollination, for this reason, parthenocarpy is an alternative to generate greenhouse zucchini varieties, so efforts are currently being made in the search for genetic parthenocarpy that does not it requires the stimulation of pollination, nor by physiological factors in order that the fruit develops in a normal way until physiological maturity. A total of 46 parthenocarpic genotypes of round zucchini shrub type squash obtained at the Autonomous University Chapingo were studied. The objective was to characterize and identify the genetic diversity among the genotypes from the variability obtained by means of molecular genetic markers such as the microsatellites of the ISSR type (inter repeated simple sequences) and RAMP (microsatellite polymorphism amplified at random). It was used (GATA)4 as an ISSR initiator and the combination of (GATA)4 with four random sequence primers of the Operon series A (OPA05, OPA10, OPA13 and OPA19) for RAMP. With the two techniques, a total of 43 polymorphic loci were obtained, six loci amplified with ISSR and 37 loci with RAMP. The percentage of polymorphic loci for ISSR was 100%, while for RAMP it was 91.8% polymorphism, a high degree of genetic relationship was found between the partenocarpal genotypes. Five groups were formed for ISSR and four for RAMP, with gene distances between 0.72 to 1.
Keywords: Cucurbita pepo L., genetic analysis, microsatellites, RAMP.